1999
DOI: 10.1212/wnl.53.4.801
|View full text |Cite
|
Sign up to set email alerts
|

DNA analysis of Huntington’s disease

Abstract: Approximately 20% of the estimated 10,000 HD patients living in Germany, Switzerland, and Austria have been identified by DNA analysis (total population, approximately 100 million; incidence of HD, 1:10,000). Assuming a ratio of HD patients to individuals at risk of 1:3, approximately 30,000 individuals are, in principle, eligible for a presymptomatic test. Less than 3 to 4% of individuals at risk have requested a presymptomatic test. This shows that the assumed enormous request of predictive testing has not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
39
0
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 18 publications
6
39
0
5
Order By: Relevance
“…[12][13][14][15][17][18][19][20][21][22] This is to be expected because 11.3% of candidates were at less than 50% risk, and individuals born at 50% risk and who present for testing as adults have a significantly lesser risk the longer they remain asymptomatic. 39,40 The fact that a proportion of the at-risk population become symptomatic and thus ineligible for predictive testing is likely to account for the gene-positive group being younger (mean age 37.1 years) than the gene-negative (42.6 years) or "reduced penetrance" candidates (55.4 years).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][17][18][19][20][21][22] This is to be expected because 11.3% of candidates were at less than 50% risk, and individuals born at 50% risk and who present for testing as adults have a significantly lesser risk the longer they remain asymptomatic. 39,40 The fact that a proportion of the at-risk population become symptomatic and thus ineligible for predictive testing is likely to account for the gene-positive group being younger (mean age 37.1 years) than the gene-negative (42.6 years) or "reduced penetrance" candidates (55.4 years).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent review by a genetics professional 3 years-and two pregnancies-later showed that although the patient's first allele (described on the first page of the laboratory report) was normal, the second allele (described on the next page of the report) had a CAG repeat expansion. Apparently the report that the physician saw was [1987] First report of prenatal exclusion testing Turner et al [1988] Prenatal testing in South Australia Turner et al [1989] Case report of detection of Down syndrome during HD prenatal testing Millan et al [1989], McIntosh et al [1989] Prenatal exclusion testing; case report Fahy et al [1989] Describes prenatal exclusion testing Tyler et al [1990] Prenatal exclusion testing Corson et al [1990] Approach to prenatal testing Spurdle et al [1991] Case report of prenatal testing with linked markers Skraastad et al [1991] Prenatal testing with linked markers in the Netherlands Thies et al [1992] Prenatal testing with linked markers in Germany Sheffield [1993] Review of methodologies Greenberg [1993], Burgess [1994] Ethical issues in prenatal testing Adam et al [1993] Canadian experience with prenatal testing using linked markers Rosser et al [1994] Prenatal testing by direct gene analysis Tolmie et al [1995] Scotland experience with prenatal exclusion testing Evers-Kiebooms et al [1996] Interaction between predictive and preimplantation testing Schulman and Black [1997] Preimplantation genetic diagnosis Braude et al [1998] Nondisclosing preimplantation genetic diagnosis Beyleveld et al [1998] Ethical and legal implications of prenatal exclusion testing Maat-Kievit et al [1999a] Ten years of experience in The Netherlands Kromberg et al [1999] Experience with prenatal testing in South Africa Laccone et al [1999] Experience with predictive and prenatal testing in Germany, Austria, Switzerland Lashwood and Flinter [2001] Preimplantation genetic diagnosis in the UK Simpson et al [2001Simpson et al [ , 2002 Prenatal testing in the UK and Europe Sermon et al [2002] Preimplantation genetic diagnosis Naruse [2002] Case...…”
Section: The Difference Between Genetic Information and Genetic Counsmentioning
confidence: 99%
“…Die besonderen Anforderungen einer prädiktiven Testung auf eine nicht behandelbare neurodegenerative Krankheit sind von der Chorea Huntington bekannt und haben zur Formulierung international gültiger Richtlinien geführt [21,22]. Studien haben gezeigt, dass eine non-direktive ausführliche humangenetische Beratung vor der Testung unverzichtbar ist [23], und dass die Mehrheit der Personen, für die ein prädiktive genetische Testung auf Chorea Huntington in Frage kommen würde, auf den Test verzichten [24]. Es erscheint daher angezeigt, die Testung auf MGA1 baldmöglichst wieder aus dem Neugeborenenscreening zu entfernen.…”
unclassified